Is the happiness of Chinese truly the highest in the world? The impact of basic public services on happiness - Mu, Na; Li, Shaoting; Wang, Zhengbing (Frontiers in Public Health, 2023)
Based on the survey report by the United Nations Sustainable Development Solutions Network (SDSN) and Ipsos Group, the world ranking of Chinese people's happiness shows a significant gap. This study attempts to analyze the subjective well-being of Chinese residents through public database from the China Household Finance Survey Center in 2017. An ordered Probit model is constructed to investigate the impact of non-monetary factors, specifically basic public services, on the subjective well-being of Chinese people. The results indicate that: (1) The subjective well-being of Chinese residents is found to be lower than what the survey report indicated. (2) Basic public services have a significant positive impact on residents' happiness. (3) Social trust played a moderating role, positively influencing the relationship between basic public services and residents' happiness. (4) The impact of basic public services on happiness varied significantly depending on factors such as age, registered residence, and places of residence. To enhance the happiness of Chinese residents, it is recommended to focus on improving the equalization of basic public services and establishing a robust basic public service system.These measures can effectively contribute to the overall well-being and happiness of the population.